Mild Nutrient Starvation Triggers the Development of a Small-Cell Survival Morphotype in Mycobacteria - Wu, Mu-Lu; Gengenbacher, Martin; Dick, Thomas (Frontiers in Microbiology, 2016)
Mycobacteria, generally believed to be non-sporulating, are well known to survive shock starvation in saline for extended periods of time in a non-replicating state without any apparent morphological changes. Here we uncover that mycobacteria can undergo cellular differentiation by exposing Mycobacterium smegmatis to mild starvation conditions. Traces of various carbon sources in saline triggered the development of a novel small resting cell (SMRC) morphotype. Development of SMRCs could also be observed for other mycobacteria, suggesting evolutionary conservation of this differentiation pathway. Fluorescence microscopic analyses showed that development of SMRCs progresses via septated, multi-nucleoided cell intermediates, which divide to generate mono-nucleoided SMRCs. Intriguingly, saline shock-starved large resting cells (LARCs), which did not show cell size or surface changes when observed by scanning electron microscopy, remodeled their internal structure to septated, multi-nucleoided cells, similar to the intermediates seen during differentiation to SMRCs. Our results suggest that mycobacteria harbor a starvation-induced differentiation program in which at first septated, multi-nucleoided cells are generated. Under zero-nutrient conditions bacteria terminate development at this stage as LARCs. In the presence of traces of a carbon source, these multi-nucleoided cells continue differentiation into mono-nuleoided SMRCs. Both SMRCs and LARCs exhibited extreme antibiotic tolerance. SMRCs showed increased long-term starvation survival, which was associated with the presence of lipid inclusion bodies.